Description of Macro Nutrition Intake, Natrium, Fiber, Physical Activity, and Blood Pressure in Hypertension Patients - Melly Juis Rapina Ayu; Afriyana Siregar; Terati Terati (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background. Hypertension is a disease in which blood pressure is ≥ 140 mmHg for systolic and ≥ 90 mmHg for diastolic. Hypertension is often called the silent killer because sufferers cannot feel the symptoms. Excess sodium intake, less fiber, and inadequate physical activity can all contribute to hypertension. This study aims to determine the picture of sodium intake, fiber, and physical activity on the blood pressure of hypertensive patients at Sukarami Health Center in Palembang.Research Methods. This kind of research uses an incidental sampling method and a cross-sectional research design and is descriptive. The sample in this study was 42 people, with a reserve of 10% to 46 people. Primary data was taken by measuring blood pressure, and interviews and secondary data were taken from the profile of the Sukarami Health Center in Palembang.Research Result. The results showed that most of the energy intake was good at 52.2%, protein intake was mainly good at 47.8%, fat intake was primarily good at 45.7%, carbohydrate intake mainly was good at 56.5%, sodium intake was mostly more 67.3%, fiber intake mainly was 78.4% less, physical activity was primarily light 56.5%, and the hypertension level was mostly mild 69.6%. Conclusion. Based on the condition of hypertensive patients, they still have more sodium intake, low fiber intake, and less physical activity. It is recommended that patients pay attention to sodium intake, fiber, and physical activity so that blood pressure becomes normal.